Strengthening Local Governance at Grassroots Level: A Study of in Himachal Pradesh - Sapna Devi (MultiTech Publisher, 2024)
This study delves into the dynamics of people's participation in grassroots democracy, with a specific focus on the northern Indian state of Himachal Pradesh. Grassroots democracy serves as the cornerstone of a vibrant and inclusive democratic system, offering citizens a direct and active role in decision-making processes at the local level. Himachal Pradesh, known for its unique blend of cultural diversity and challenging terrain, provides a compelling backdrop to investigate the multifaceted aspects of community engagement and governance. This research employs a multidisciplinary approach, combining qualitative and quantitative methods, to analyze the patterns and determinants of citizen involvement decentralized governance structures in the state. It explores the mechanisms through which individuals and communities engage with the democratic process, shedding light on the impact of local socio-cultural contexts and the role of government institutions in facilitating or hindering participation. By examining the case of Himachal Pradesh, this study not only contributes to our understanding of grassroots democracy in India but also offers insights that are applicable to similar contexts worldwide. The findings highlight the significance of fostering a culture of citizen participation, building the capacity of local governments, and creating inclusive platforms for dialogue between communities and authorities. Ultimately, this research underscores the pivotal role that people play in shaping the future of their local communities and, by extension, the democratic landscape of a nation.